A Review of Operational Conditions of the Agroforestry Residues Biomethanization for Bioenergy Production Through Solid-State Anaerobic Digestion (SS-AD) - Dhaouefi Zaineb; Lecoublet Morgan; Taktek Salma; Lafontaine Simon; LeBihan Yann; Braghiroli Flavia Lega; Horchani Habib; Koubaa Ahmed (Energies)
Agroforestry residues are a promising source of organic matter and energy. These organic wastes are often poorly managed by incineration or open-air composting, resulting in the emission of greenhouse gases. Solid-state anaerobic digestion has recently attracted considerable attention to converting organic waste with a high total solids content, such as agroforestry residues, into renewable energy. However, the complex structure of these residues is still a defiance to this technology. Their degradation requires a long period, resulting in low heat and mass transfer. In addition, the process is often inhibited by the accumulation of toxic compounds. An efficient management process has remained under development. Comprehending the challenges faced when treating agroforestry waste is necessary to create practical applications. This review provides essential information for more effective management of complex agricultural and forestry residues using the SS-AD process. It covers the different parameters and experiments that have successfully managed these residues for renewable energy production. Various solutions have been identified to overcome the drawbacks encountered. These include co-digestion, which brings together different residues for better sustainability, and the strategies used to improve energy production from these residues at different levels, involving efficient pretreatments and appropriate operational reactor designs.